Interactions between Social Media and E-service Quality of Online Travel Agencies in Nigeria - Ogunmokun, Oluwatobi Adeyemi (Eastern Mediterranean University EMU, 2017)
The objective of this study is to examine in what way and to what extent does social media influence the quality of electronic services online travel agencies offer, from the consumer’s perception. A few e-service dimensions have been introduced in past researchers. Only a few of these investigated the influence social media have on the quality of e-service, especially now that advancement in technology has allowed for interfaces between personnel and consumers as well as amongst consumers. These interfaces have been said to have considerable influences on e-service quality. Gleaning from dimensions of e-service quality already identified by scholars, dimensions were put together to examine how reviews on online travel agencies’ websites could influence quality of services provided. Parasuraman et al., (2005) established that perceived value is enhanced by service quality which subsequently enhances the customer’s loyalty intention. Thus, dimensions of e-service quality were used to investigate online reviews on online travel agencies’ websites and the influence it has on perceived quality and loyalty intention. Findings from the investigation suggested that information and content quality dimension of online travel reviews drives e-service quality. This was the result following a multiple regression analysis. The import of this is that when an online travel agency increases the information and content quality of the reviews on its website, the website user’s perceived value increases and this subsequently heightens the user’s loyalty intention. Keywords: Online Travel Agencies, Social Media, E-service Quality

ÖZ: Bu çalışma sosyal medyanın elektronik seyahat hizmetleri nin kalitesine ne ölçüde etki ettiğini araştırmaktadır. Elektronik hizmet boyutları daha önce araştırılmış olmakla birlikte sosyal medya etkinliklerinin elektronik hizmet kalitesi üzerindeki etkileri henüz bilinmemektedir. Teknolojik gelişmeler sayesinde müşteri ile şirket arasındaki iletişim kanalları zenginleşmiş ve bu arayüzlerin elektronik hizmet kalitesi üzerinde ciddi etkileri oluşmuştur. Parasuraman ve arkadaşlarının yaptığı bir çalışmaya göre (2005), hizmet kalitesi müşteri sadakatini artırmaktadır. O yüzden, elektronik hizmet kalitesinin elektronik seyahat müşteri lerinin sadakati üzerindeki etkisi de çalışılmıştır. Çalışmanın sonuçları elektronik seyahat hizmetlerinin kalitesi için iki boyutun önemini işaret etmiştir; bunlar bilgi ve içerik olmaktadır. Ayrıca sosyal medya etkinliklerinin müşteri sadakatini artırdığı bulunmuştur. Anahtar Kelimeler: Çevrimiçi seyahat acenteleri, Sosyal Medya, E-Hizmet Kalitesi
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Supervisor: Assoc. Prof. Dr. Selcan Timur.
Keywords: Business Administration; Marketing Management; Travel Agencies-E-Commerce; Online Travel Agencies; Social Media; E-service Quality